Mismatch of Cultural Dimensions in an Urban Medical Educational Environment. (21st October 2013) - Malone, Bethany; Hasan, Stephania; Sanni, Aliu; Reilly, James
Abstract : Objective . To identify cultural dimensions and their potential mismatches between attending physicians and their residents and medical students. Methods . We surveyed faculty and students, both undergraduates and postgraduate resident physicians, at the SUNY Downstate College of Medicine, using Hofstede's VSM-08 questionnaire, and calculated cultural dimensions, including the Power-Distance Index (PDI), Individualism (IDV), Masculinity (MAS), Uncertainty Avoidance Index (UAI), and Long-term Outlook (LTO). Correlations between faculty and student demographic data and cultural dimensions were calculated (SPSS). Results . There were 237 student and resident respondents and 96 faculty respondents. Comparing all faculty and student respondents, significant differences were found in four of five cultural dimensions, with faculty scoring higher in MAS, and lower in PDI, IDV, UAI, and LTO. Conclusions . These differences may be important in the design and implementation of a medical educational curriculum, and, particularly, in the measurement and evaluation of educational outcomes.